Glacial geomorphology of the central sector of the Cordilleran Ice Sheet, Northern British Columbia, Canada - Dulfer, Helen E.; Margold, Martin (Taylor & Francis, 2021)
Northern British Columbia was repeatedly covered by the Cordilleran Ice Sheet (CIS) during the glacial periods. However, its mountainous terrain and remote location have thus far impeded our understanding of the central sector of the ice sheet. The improved resolution of remotely sensed data provides new opportunities to unravel the glacial history of this inaccessible location. Here, we present a comprehensive map of glacial landforms for the central sector of the CIS (55° to 60° N). Seven landform categories were mapped: ice flow parallel lineations, moraines (CIS outlet glacier moraines, Late Glacial moraines and moraines of unknown origin), meltwater channels (lateral and submarginal, subglacial, proglacial, and meltwater channels of unknown origin), kame terraces, eskers (single ridges and esker complexes), perched deltas and subglacial ribs. Collectively, these landforms provide a record of the extent, thickness and behaviour of the CIS, the direction of its movement and pattern of ice retreat.